Energy consumption of air conditioning units in Khon Kaen - Wongwuttanasatian, Dr.Thanakorn (Engineering and Applied Science Research, 2013)
This project is a study for energy consumption of air conditioners in Khon Kaen province, focusing on domestic use and office buildings. The study was conducted by sampling survey in many urban villages and office buildings in Khon Kaen for ten months. From results of the survey and data analysis, it was found that energy consumption in air conditioners accounted for 38% of the electricity bill in the case of houses, and 46% in the case of office buildings. In addition, the  proportions of electricity due to using of air conditioners were different in each month depending on the seasons around the year, It can be concluded that as in summer season during April, the proportions were; 53% for houses and 54% for office buildings. These proportion values are indicators of the required energy bill for air conditioner-consumed compared with other electric equipment. Consequently, this finding may lead to further studies of energy saving strategies of using air-conditioners.